2023
DOI: 10.1126/science.add1250
|View full text |Cite
|
Sign up to set email alerts
|

Short tandem repeats bind transcription factors to tune eukaryotic gene expression

Connor A. Horton,
Amr M. Alexandari,
Michael G. B. Hayes
et al.

Abstract: Short tandem repeats (STRs) are enriched in eukaryotic cis -regulatory elements and alter gene expression, yet how they regulate transcription remains unknown. We found that STRs modulate transcription factor (TF)–DNA affinities and apparent on-rates by about 70-fold by directly binding TF DNA-binding domains, with energetic impacts exceeding many consensus motif mutations. STRs maximize the number of weakly preferred microstates near target sites, thereby increasing TF density, with im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 187 publications
(230 reference statements)
0
15
0
Order By: Relevance
“…It has been reported that short tandem repeats (STRs) are enriched in gene promoters and variable repeat number is associated with the gene expression (Sawaya et al, 2013; Vinces, Legendre, Caldara, Hagihara, & Verstrepen, 2009). Furthermore, approximately 90% of transcription factors preferentially bind to STRs (Horton et al, 2023). Therefore, we also analyzed the presence of STRs in the updated draft genome using TRF v4.09 (Benson, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that short tandem repeats (STRs) are enriched in gene promoters and variable repeat number is associated with the gene expression (Sawaya et al, 2013; Vinces, Legendre, Caldara, Hagihara, & Verstrepen, 2009). Furthermore, approximately 90% of transcription factors preferentially bind to STRs (Horton et al, 2023). Therefore, we also analyzed the presence of STRs in the updated draft genome using TRF v4.09 (Benson, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The high copy numbers of (AT)n repeat motif in exome captures could be partially explained by the sequencing of TATA boxes located close to transcription start sites. The mononucleotide repeat (A)n and many other short tandem repeats have been linked to cis -regulatory elements in gene expression regulation in eukaryotes (Horton et al, 2023; Pholtaisong et al, 2022), explaining their abundance in exome captures. However, the abundance of poly-G repeats is a common artifact in two-channel Illumina sequencing systems observed when the dark base G is called after the termination of synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…We introduce a sequence diversity metric, defined as the average k-nearest neighbor (KNN) distance between a sequence and its neighbors from the same group, to quantify how similar designed sequences are to each other. Human regulatory DNA exhibits elevated GC content [20] and an abundance of particular subsequences like of GATA motifs [21], CpG islands [21], and short repeats [22]. Evaluating sequence composition with our quantitative metrics could therefore provide insight into the novelty and "humanness" of computationally designed CREs.…”
Section: Sequence Composition Analysismentioning
confidence: 99%